Forest tourism and recreation: case studies in environmental management. - Font, X.; Tribe, J. (Wallingford :CABI Publishing, 1999)
The demand for ecotourism and outdoor recreation is increasing and the pressures on land use are becoming more obvious. A large part of the experience of ecotourism and recreational landscape depends on the maintenance of forested land. Effective management of tourism and recreation in forests can provide extra income to help offset the costs of sustainable timber production and encourage biodiversity conservation. This book considers the compatibility between tourism, forestry and conservation, the management of natural resources and the involvement of stakeholders and the community. After an introductory chapter, issues are presented through 16 case studies (chapters 2-17) from a range of countries, including the UK, Canada, Costa Rica, Estonia, Nepal, New Zealand and Singapore. Topics covered include national parks, peri-urban forestry and wilderness management, as well as practitioner orientated contributions from the UK (on Center Parcs, the National Trust and the Forest of Mercia). The case studies are arranged in 2 sections: Part I, Issues and problems (2-10); and Part II, Strategies and solutions (11-17). The book provides a challenging review for both academic and professional readers in tourism and recreation, environmental conservation and rural geography.
Keywords: EE112 - Forestry Economics, (New March 2000); EE115 - Natural Resource Economics, (New March 2000); KK100 - Forests and Forest Trees (Biology and Ecology); KK110 - Silviculture and Forest Management; KK160 - Ornamental and Amenity Trees; PP300 - Land Resources; PP700 - Biological Resources (General); UU625 - Sport and Recreational Activities, (New March 2000); UU700 - Tourism and Travel; Canada; Costa Rica; Estonia; Nepal; New Zealand; Singapore; UK